The effectiveness of school leadership on teachers’ performance and students’ achievement: A case study of a private school in Dubai - DABASH, ALAA NAIM ALI (2018)
An effective and successful leadership is considered as the significant aspect in the educational environment. The responsibility of a principal in the school is to exhibit the leadership behavior so that teachers can perform in the efficient manner and students’ achievement is feasible. There is no ambiguity that leadership holds the effective influence on the entire environment of the school. This research aims to analyze the effectiveness of the school leadership on the performance of the teacher and the achievement of the students studying in the schools of Dubai. Another aim of this dissertation is to explore the link between the leadership styles followed in the schools, and qualified principals, leading to professional development of teachers. In order to carry out this research, the approach of qualitative and quantitative methods was taken into consideration i.e. this research is based on interviews and survey for primary research and literature review for secondary research. The results of this study show that leadership behavior of the school principal is potential to significantly enhance the performance of the teachers as well as the achievements of the students. The literature has suggested that supportive leadership style of participative leadership style of school principals are the most appropriate leadership styles in schools in order to enhance the performance of teachers and achievements of students.